Commodity Pricing during Covid-19 Pandemic: Jurisprudence Comparison Study: Comparing the Decisions Issued by the Ministry of Trade and Industry in Kuwait - Alelewi , Bader M (Dirasat: Shari'a and Law Sciences, 2021)
The research paper dealt with the rule of commodity pricing during Covid-19 by comparing it with the decisions of the ministry of commerce and ‎industry in Kuwaiti. Firstly, the researcher undertook the jurisprudence study in a fundamental ‎way, then implemented them with refence to the impact of the Covid-19 pandemic‏. The researcher started with a brief introduction about Covid-19 and pricing in gevneral. Then expalining the rule of pricing when needed and not, indicating in that the liberation of the dispute and the cause of the dispute and the correct saying. And indicating what the pricing enters and who is, and the rule of approval of pricing and violation, and its impact on the sale, and obey the Guardian, and taizir. Additionally, focusing on how to price and the rules of permissible pricing ‎from the jurisprudential aspect‏. As for the implementation aspects, the reseacher showed the decisions of the Kuwaiti ‎Ministry of Commerce and Industry, then showed the extent to which these decisions adhered to the rights of the trader and the consumer, and ‎their compliance with the objectives of Sharia‏.‏ After that, the author explained the ruling of this decision from the jurisprudential ‎aspect in Sharia based on what has been studied from the jurisprudential aspect of ‎the study in relation to the Covid-19 pandemic.‏ In conclusion, the research draws a summary in which he presented the most ‎important findings and recommendations.